Család, korporáció, állam: A ,tudat’ kommunikatív felfogása Durkheimnél (Szociológiai Szemle, 2024)
Durkheim’s writings and lectures from the second half of the 1890s, discussing the family, the corporations, and the state, point to a sociology of knowledge that is different from, and less well-known than, his later version of the sociology of knowledge. In this conception, communication plays a central role. Intensive relationships and high social density produce specific ideas within families and corporations and more universal, integrative ones within a state. For this approach to the sociology of knowledge, the main question is no more the relation between ’existential base’ and ’spiritual products’.